Design and performance of stone mastic asphalt in Singapore conditions - Qiu, Yunfeng (2008)
Stone Mastic Asphalt (SMA) mixtures are gap-graded mixtures that contain a coarse aggregate skeleton and a high asphalt binder content mortar. The rutting resistance is mostly attributed to the coarse aggregate skeleton component that exhibits “stone-to-stone” contact due to its gap-graded gradation. The objective of the research is to provide a methodology of quantifying coarse aggregate stone-to-stone contact in SMA with different aggregate packing to yield high rutting resistance; thus, developing a new mix design procedure and leading to an improved SMA mixture design and performance. A total of thirty-seven mixtures were tested in this study for developing and analysing coarse aggregate stone-to-stone contact in SMA mixtures.